The Neurotrophins Nerve Growth Factor, Brain-derived Neurotrophic Factor, Neurotrophin-3, and Neurotrophin-4 Are Survival and Activation Factors for Eosinophils in Patients with Allergic Bronchial Asthma - Nassenstein, Christina (The Rockefeller University Press, 2003)
Neurotrophins (nerve growth factor [NGF], brain-derived neurotrophic factor [BDNF], neurotrophin [NT]-3, and NT-4) have been observed in elevated concentrations in allergic diseases. Neurotrophin levels are up-regulated endobronchially after allergen challenge. This coincides with an influx of activated eosinophils into the bronchial lumen. These eosinophils have an increased viability and CD69 expression 18 h after segmental allergen provocation (SAP) which is not present in peripheral blood. To investigate whether these observations are related we studied the influence of neurotrophins on eosinophil function in allergic asthma. Incubation with NGF, BDNF, NT-3, or NT-4 caused a significant increase in the viability and CD69 expression of isolated eosinophils from bronchoalveolar lavage fluid (BALF) but not from peripheral blood, suggesting a unique sensitivity of endobronchial eosinophils to neurotrophins. To elucidate the underlying mechanisms expression of the neurotrophin receptors p75NTR, trkA, trkB, and trkC on eosinophils was analyzed by RT-PCR and immunocytology. After SAP expression of all neurotrophin receptors was markedly elevated on eosinophils from BALF. Our findings suggest that neurotrophin-mediated activation of bronchial eosinophils might play a role in the regulation of eosinophilic inflammation in allergic asthma.